Genetics from Laboratory to Society
XIII, 222 p.
Keywords: Based on detailed studies of the actual use of genetic testing in context, this book looks at the ethical and political questions raised by the expanding role of genetic information in society. In contrast to the established perspective which focuses on individual freedom, the authors emphasize a pragmatic approach focussed on societal learning.